PHYSICAL AND CHEMICAL PROPERTIES OF ORGANIC MINERAL ADDITIVE FOR RUMINANT THROUGH BIOLOGICALLY INCORPORATED BY SACCHAROMYCES CEREVISIAE IN DIFERENCE SUBSTRATES - Ahmad Sofyan; Hendra Herdian; Awistaros Angger Sakti; Gumilang Khairulli; Anuraga Jayanegara (Research Center for Chemistry - LIPI, 2015)
This research was conducted to evaluate physical and chemical properties of organic mineral additive incorporated by Saccharomyces cerevisiae which was cultivated on different growth media consisted of cassava flour and rice bran, respectively. Treatment was arranged on completely randomized design consisted of rice bran without inoculants (RBo), rice bran with inoculants (RBi), cassava flour without inoculants (CFo), cassava flour with inoculants (CFi). Substrates were fortified by microminerals contained of Cu (100 ppm), Mn (100 ppm), Zn (100 ppm), I (10 ppm), Fe (2.5 ppm) and Co (2 ppm). Inoculation of S. cerevisiae could reduce fungal contamination. Physical characteristic of cassava flour was better in flavour and texture than rice bran in which tends to rancidity. Nutrients composition was similar in cassava and rice bran however crude fibre content in rice bran tends to be higher after fermentation. Mineral content (Zn and Fe) relatively decreased and in substrate supplemented by inoculant and rice bran had higher than cassava. In summary, micromineral was incorporated in cassava flour with inoculated S. cerevisiae had better than rice bran.Keywords: Organic mineral, cassava flour meal, S. cerevisiae, rice bran, ruminant.